Social Video Content Delivery - Wang, Zhi; Liu, Jiangchuan; Zhu, Wenwu (SpringerBriefs in Electrical and Computer Engineering, 2016)
This brief presents new architecture and strategies for distribution of social video content. A primary framework for socially-aware video delivery and a thorough overview of the possible approaches is provided. The book identifies the unique characteristics of socially-aware video access and social content propagation, revealing the design and integration of individual modules that are aimed at enhancing user experience in the social network context. The change in video content generation, propagation, and consumption for online social networks, has significantly challenged the traditional video delivery paradigm. Given the massive amount of user-generated content shared in online social networks, users are now engaged as active participants in the social ecosystem rather than as passive receivers of media content. This revolution is being driven further by the deep penetration of 3G/4G wireless networks and smart mobile devices that are seamlessly integrated with online social networking and media-sharing services. Despite increasingly abundant bandwidth and computational resources, the ever-increasing volume of data created by user-generated video content--along with the boundless coverage of socialized sharing--presents unprecedented challenges. .